Weak Cross-Species Relationships between Body Size and Trophic Level Belie Powerful Size-Based Trophic Structuring in Fish Communities - Jennings, Simon; Pinnegar, John K.; Nicholas V. C. Polunin; Boon, Trevor W. (The Journal of animal ecology, 2001)
1. Body size determines rates of respiration and production, energy requirements, mortality rates, patterns of predation and vulnerability to mortality. Body size distributions are often used to describe structure and energy flux in communities and ecosystems. 2. If clear relationships can be established between body size and trophic level in fishes, they may provide a basis for integrating community and ecosystem analyses based on size spectra, food webs and life histories. 3. We investigated relationships between the body sizes (weight and length) of north-east Atlantic fishes and their trophic level. The abundance of15N, as determined by stable isotope analysis, was used as an index of trophic level. 4. Cross-species and comparative analyses demonstrated that body size was unrelated or weakly related to trophic level. Thus allometric relationships between body size and trophic level could not be used to predict the trophic structure of fish communities. 5. The results of the cross-species analyses contrasted with patterns in the size and trophic structure of entire fish communities. When fish communities were divided into size classes, there were strong positive relationships between size class and trophic level. The slope suggested a mean predator: prey body mass ratio of 80: 1. 6. Our results suggest that body size does not provide a useful surrogate of trophic level for individual species, but that body size is an excellent predictor of trophic level within the community, providing an empirical basis for integrating community analyses based on models of trophic structure and body size distributions.